Determination of Trace Potassium in Concentration Salt Solution by Anti-Fluorescence Quenching Method on Rhodamine B-Sodium Tetraphenylborate System - Lei, Xiangrong; Wei, Xiaoling; Gong, Qi; Wei, Qiuyang; Wang, Lisheng (Asian Journal of Chemistry, 2012)
It is found that sodium tetraphenylborate had the ability to quench the fluorescence of Rhodamine B, could make the intensity of fluorescence weak or even disappear. But K+, which can reacted with the sodium tetraphenylborate to form precipitation had the anti-quenching effect on Rhodamine B-sodium tetraphenylborate system, enhanced the intensity of fluorescence. The fluorescent signal enhancement degree was proportional to the concentration of K+. Using antifluorescence quenching method, with 375 nm for excitation wavelength and 640 nm for emission wavelength, the fluorescence intensity F1 and F0 of solution and blank solution were measured. The different value DF = F1-F0 was proportional to the concentration of K+. Based on these, a new, simple and sensitive antifluorescence quenching method for determination of K+ was established. The linear relationship between the different value DF of the intensity of fluorescence and the concentration of K+ is in the range of 2.14 mg L-1-43.0 mg L-1. The detection limit is 0.642 mg L-1 and the relative standard deviation is 1.32 %. This method can be used for determination of trace potassium in concentration salt solution and has been successfully applied to determination of K+ in common salt and compound sodium chloride injection with satisfactory results.